The function of VAMP2 in mediating membrane fusion: An overview - Yan, Chong; Jiang, Jie; Yang, Yuan; Geng, Xiaoqi; Dong, Wei (Frontiers in Molecular Neuroscience, 2022)
Vesicle-associated membrane protein 2 (VAMP2, also known as synaptobrevin-2), encoded by VAMP2 in humans, is a key component of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex. VAMP2 combined with syntaxin-1A (SYX-1A) and synaptosome-associated protein 25 (SNAP-25) produces a force that induces the formation of fusion pores, thereby mediating the fusion of synaptic vesicles and the release of neurotransmitters. VAMP2 is largely unstructured in the absence of interaction partners. Upon interaction with other SNAREs, the structure of VAMP2 stabilizes, resulting in the formation of four structural domains. In this review, we highlight the current knowledge of the roles of the VAMP2 domains and the interaction between VAMP2 and various fusion-related proteins in the presynaptic cytoplasm during the fusion process. Our summary will contribute to a better understanding of the roles of the VAMP2 protein in membrane fusion.